2007
DOI: 10.1021/bc060281l
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Gastrin-Releasing Peptide Receptor-Positive Tumors in Mice Using64Cu- and86Y-DOTA−(Pro1,Tyr4)-Bombesin(1−14)

Abstract: Bombesin is a tetradecapeptide neurohormone that binds to gastrin-releasing peptide receptors (GRPR). GRPRs have been found in a variety of cancers including invasive breast and prostate tumors. The peptide MP2346 (DOTA-(Pro(1),Tyr(4))-bombesin(1-14)) was designed to bind to these GRP receptors. This study was undertaken to evaluate radiolabeled MP2346 as a positron emission tomography (PET) imaging agent. MP2346 was radiolabeled, in high radiochemical purity, with the positron-emitting nuclides (64)Cu (t(1/2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
86
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 37 publications
0
86
0
1
Order By: Relevance
“…The 64 Cu-DOTA conjugates usually exhibit a high accumulation of liver radioactivity (17,24) because of the dissociation of 64 Cu in vivo from DOTA, followed by metabolism and transchelation to other proteins (16,25,26). NOTA is most commonly used for 68 Ga (half-life, 68 min) labeling because the rapid reaction kinetics of NOTA match the short half-life of 68 Ga. NOTA was also reported to be labeled with 64 Cu, with reduced liver accumulation (15).…”
Section: Discussionmentioning
confidence: 99%
“…The 64 Cu-DOTA conjugates usually exhibit a high accumulation of liver radioactivity (17,24) because of the dissociation of 64 Cu in vivo from DOTA, followed by metabolism and transchelation to other proteins (16,25,26). NOTA is most commonly used for 68 Ga (half-life, 68 min) labeling because the rapid reaction kinetics of NOTA match the short half-life of 68 Ga. NOTA was also reported to be labeled with 64 Cu, with reduced liver accumulation (15).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies in PC-3-bearing mice, 67 Ga-PESIN, 177 Lu-AMBA, and 99m Tc-demobesin-1 showed tumor uptake of 14.8, 6.4, and 16.2 %ID/g, respectively (9,(25)(26)(27)(28). Variation in amounts of peptides, mouse strain (species, sex, and weight), tumor cells (passage number, culture conditions) used, tumor size, and vascularization of the tumor may all be factors that affect tumor uptake and tumor-to-non-tumor ratios.…”
Section: Discussionmentioning
confidence: 77%
“…The uptake of the 64 Cu-labeled NOTA-8-Aoc-BBN (7)(8)(9)(10)(11)(12)(13)(14) conjugate in PC-3-bearing mice (3.59 6 0.70 % ID/g, 1 h after injection) was similar to the tumor uptake for our radiolabeled compounds (2.15-1.24.%ID/g, 1 h after injection) (16). However, Lears et al recently reported in this tumor model a tumor uptake as high as 13.0 %ID/g at 1 h after injection using 64 Cu-labeled SarAr-SA-Aoc-BBN(7-14) (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the GRPR is over-expressed on the surface of T-47D breast carcinoma cells while being absent from normal breast tissues (Giacchetti et al, 1990). This receptor has served as a target for a number of diagnostic and therapeutic strategies Garrison et al, 2007;Parry et al, 2007;Biddlecombe et al, 2007;Guojun et al, 2008;Zhou et al, 2003;Ma et al, 2007). T-47D xenografts in mice have been used in preclinical investigations of a variety of diagnostic modalities (Giblin et al, 2006;Aliaga et al, 2004).…”
Section: Grpr-expressing T-47d Human Bbreast Cancer Cellsmentioning
confidence: 99%